Second language experience influences salience of phonological units in spoken word production in the first language. (December 2021) - Wang, Jie; Wong, Andus Wing-Kuen; Chen, Hsuan-Chih
Research question: Previous research suggests that the grain size of primary phonological units (PUs) in spoken word production is language-specific (e.g., phonemic segments in Germanic languages, and atonal syllables in Chinese). When the two languages of bilingual speakers have different primary PUs in their native speakers, will first language (L1) phonological processing be influenced by second language (L2) experience? Methodology: In a picture–word interference task, native Chinese speakers who spoke English as L2 were required to say aloud the predesignated L1 name of a picture while ignoring a written L1 character superimposed on the picture. The picture name shared a certain phonological component (i.e., rhyme or atonal syllable) with the distractor in the related condition but not in the unrelated condition. Data and analysis: Data of 186 participants from eight originally independent experiments were pooled. Multiple regression analyses were conducted on subject means to investigate whether the effects of rhyme relatedness and syllable relatedness on L1 naming latency were influenced by L2 self-rated proficiency, age of acquisition (AoA), and/or years of use. Trial-by-trial data were then analyzed with linear mixed-effects modeling. Findings: Both the rhyme effect and the syllable effect increased with years of L2 use, indicating that the salience of PUs in L1 spoken word production can be influenced by L2 experience. Originality: The current study adopted a chronometric approach to investigate the influence of L2 experience on phonological processing during L1 spoken word production. Importantly, multiple aspects of L2 experience (i.e., self-rated proficiency, AoA, and years of use) were examined at the same time in a relatively large sample. Implications: The current findings provide evidence for backward transfer of primary PUs in spoken word production, which demonstrates the plasticity of the phonological encoding process in bilingual speakers. These findings are discussed and compared with cross-language transfer of phonological awareness in the discussion.